2023
DOI: 10.3390/vaccines11020282
|View full text |Cite
|
Sign up to set email alerts
|

The BNT162b2 mRNA COVID-19 Vaccine Increases the Contractile Sensitivity to Histamine and Parasympathetic Activation in a Human Ex Vivo Model of Severe Eosinophilic Asthma

Abstract: The BNT162b2 COVID-19 vaccine is composed of lipid-nanoparticles (LNP) containing the mRNA that encodes for SARS-CoV-2 spike glycoprotein. Bronchospasm has been reported as an early reaction after COVID-19 mRNA vaccines in asthmatic patients. The aim of this study was to investigate the acute impact of BNT162b2 in a human ex vivo model of severe eosinophilic asthma. Passively sensitized human isolated bronchi were challenged with the platelet-activating factor to reproduce ex vivo the hyperresponsiveness of ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“… 2 , 3 The available evidence suggests that COVID-19 vaccination is the dominant strategy against severe outcomes and mortality of COVID-19, 4 while asthmatic patients were considered a higher risk group for severe bronchospasm after COVID-19 vaccine injection. 5 Then asthma was also identified as an independent variable that was significantly associated with low vaccination rates. 6 Additionally, the Barcelona study showed that asthmatic patients were not susceptible to the SARS-CoV-2 virus, on the contrary, patients with T2 asthma were even immune to the virus to a high degree.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 The available evidence suggests that COVID-19 vaccination is the dominant strategy against severe outcomes and mortality of COVID-19, 4 while asthmatic patients were considered a higher risk group for severe bronchospasm after COVID-19 vaccine injection. 5 Then asthma was also identified as an independent variable that was significantly associated with low vaccination rates. 6 Additionally, the Barcelona study showed that asthmatic patients were not susceptible to the SARS-CoV-2 virus, on the contrary, patients with T2 asthma were even immune to the virus to a high degree.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this worrying percentage fully justifies the search for new and improved therapies to treat these conditions. Unfortunately, the costs and time necessary for the development and approval of new effective drugs for the treatment of chronic obstructive respiratory disorders are increasing (Calzetta, Chetta, et al, 2023a) and apart from the introduction of some monoclonal antibodies (mAbs) for the treatment of severe asthma and COPD with type 2 inflammation, the cornerstone treatments used in the majority of patients with asthma or COPD still remains focused on pharmacological classes of drugs that have been around for decades, such as bronchodilators and corticosteroids (Bhatt et al, 2023; GINA, 2023a; GOLD, 2023). Certainly, mAbs have significantly changed the management of severe asthma, however their use is restricted to a small proportion of patients (GINA, 2023b).…”
Section: Introductionmentioning
confidence: 99%
“…approval of new effective drugs for the treatment of chronic obstructive respiratory disorders are increasing(Calzetta, Chetta, et al, 2023a) and apart from the introduction of some monoclonal antibodies (mAbs) for the treatment of severe asthma and COPD with type 2 inflammation, the cornerstone treatments used in the majority of patients with asthma or COPD still remains focused on pharmacological classes of drugs that have been around for decades, such as bronchodilators and corticosteroids(Bhatt et al, 2023; GINA, 2023a; …”
mentioning
confidence: 99%